Kritik Nalar Urgensi Alur Novel "Tuhan, Izinkan Aku Menjadi Pelacur" Karya Muhidin Dahlan - Wildan Wildan (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
Kiran is the major character in the novel Tuhan, Izinkan Aku Menjadi Pelacur by Muhidin Dahlan. She is a moeslem student who was in the process of a spiritual journey to understand the concept of divinity. Great desire to know more about Islam encouraged Kiran to enter the Islamic organizations and actively participated invarious studies that drove her into an activist who fought to uphold Islamic State. However, the spiritual journey and the struggle she had committed in eagerness had failed to be actualized for she was disappointed with the attitude of her friends in arms that did not run the organization based upon Islamic rules (syariat). As a form of revenge, Kiran eventually became a prostitute.